Purely Infinite, Simple $C^*$-Algebras Arising from Free Product Constructions, II - Dykema, Kenneth J. (MATHEMATICA SCANDINAVICA, 2002)
Certain reduced free products of $C^*$-algebras with respect to faithful states are simple and purely infinite.